2012
DOI: 10.15376/biores.7.4.5435-5447
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnesium Silicate From Wheat Husk Ash: Effects of Parameters on Structural and Surface Properties

Abstract: In the present study, magnesium silicate was produced by using wheat husk ash. Wheat husk was burned at 600 °C to obtain an amorphous ash structure, and the ash was processed with sodium hydroxide solution with heat to extract silica. Sodium silicate solution and magnesium salts were used to synthesize magnesium silicate. The present study investigates effects of the feeding rate on magnesium silicate production (0.6 mL/min, 35 mL/min, 70 mL/min), the type of magnesium salt (MgSO 4 • 7H 2 O or MgCl 2 • 6H 2 O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…By increasing the particle size, the number of particles decreases, and hence surface area starts decreasing and ultimately the adsorption capacity is decreased [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the particle size, the number of particles decreases, and hence surface area starts decreasing and ultimately the adsorption capacity is decreased [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…of alkaline metals and sodium silicate solution. To date, barium, calcium, and magnesium silicate were prepared using wheat husks as a renewable silica source. These studies indicated that wheat husk can be used as a novel raw material to produce metal silicates.…”
Section: Wheat Husk Silica‐based Materialsmentioning
confidence: 99%
“…Various agricultural wastes such bagasse husk, barley husk, and rice husk have been utilized as a low‐cost, surplus silica sources around the world. Among the wastes, wheat husk has been recently used as a novel silica source due to its noteworthy silica content that was obtained from earth during the growth process …”
Section: Introductionmentioning
confidence: 99%
“…There are also many studies focused on the utilization of biomass ash in various fields, for example, as a raw material for ceramic products (Abraham et al 2013), as an adsorbent (Vassilev et al 2013;Maneerung et al 2016), as a potential source of SiO2 (Terzioglu and Yucel 2012;Terzioglu et al 2013), as a construction and building material (Adesanya and Raheem 2010), as a soil amendment (Umamaheswaran and Batra 2008;Pan and Eberhardt 2011), and as a source for potash production (Ogundiran et al 2011). However, research on the physicochemical properties of CCA obtained from biomass gasification plants is limited, and its physicochemical behavior remains uncertain.…”
Section: Introductionmentioning
confidence: 99%